Enhancing and Measuring Consumers' Motivation, Opportunity, and Ability to Process Brand Information from Ads - MacInnis, Deborah J.; Moorman, Christine; Jaworski, Bernard J. (Journal of Marketing, 1991)
Deborah J. MacInnis, Christine Moorman, Bernard J. Jaworski, Enhancing and Measuring Consumers' Motivation, Opportunity, and Ability to Process Brand Information from Ads, Journal of Marketing, Vol. 55, No. 4 (Oct., 1991), pp. 32-53